GROWING GRAPES IN A GREENHOUSE IS A NEW REVOLUTION - Ullah, Izhar (Journal of Natural Sciences and Learning, 2024)
Grapes (Vitis vinifera L.) is amongst the well-known fruits around the world. They are not only admire due to nutraceutical and extraordinary  properties but also for the multiple uses, viz, wines, juices, raisins and fresh consumption, along with side uses as in medicines and molasses etc. The modern world is facing problems of climate change, water shortage, land limitations and multiple fold increase in population. In order to meet the needs of the ever-increasing human population, intensive cultivation with limited resources is vital. Greenhouse cultivation is one of the best options for production of delicate fruits like grapes, having specific environmental requirements for giving bumper commercial crop. Precision viticulture, adopted under greenhouse conditions helps in improving the quality and quantity of produce, without compromising environmental and economic aspects. Smart choice of rootstock, efficient irrigation method, justified pruning and training of vines, timely application of just the right amount of nutrients, proper management of growth media, temperature and humidity control according to the needs of the particular growth stages of plant and controlled pollination can make possible the availability of out of season crop. This system also provides opportunities for agrotourism and a more controlled environment for future research. Installment of greenhouse demands a lot of investment both in terms of money and expertise but once established, the returns are multiple fold compared to the early investment.